(untitled) (Research, Society and Development, 2020)
Bearing in mind that the teaching of statistics and probability enables critical development in students, this experience article presents the handling of playful resources aimed at the mathematics classroom, whose target audience was high school students, in which the objective was to enhance students’ perception of statistics present in their daily lives. Regarding the methodology, studies related to critical statistical education were used as a theoretical contribution in which they defend the teaching of statistics related to problematization and critical awakening as an instrument in development when observing these concepts present in everyday life, since it is knowledge that the teaching of statistics through the mathematics teacher is often not presented or demonstrated without intertwining it with situations experienced daily. The students’ report showed that the use of playfulness to employ the concept of statistics and probability in conjunction with problematization and the possibility of group discussion favored significant learning.